Short-Term and Long-Term Effects of Climatic and Non-Climatic Factors on Maize Yield over a 33 Year Period (1990–2022) in Nepal - O. Poudel; B. B. Khatri; P. Acharya; D. R. Sharma (Journal of Applied Sciences and Environmental Management)
The objective of this paper was to investigate the short-term and long-term effects of climatic and non-climatic factors on maize yield over a 33 year period (1990–2022) in Nepal using an Autoregressive Distributed Lag (ARDL) model. The study examines the role of temperature, rainfall, pesticide use, and carbon dioxide (CO2) emissions (per capita and agricultural) in shaping maize productivity. The results show that temperature has an insignificant long-run influence on maize yield. Rainfall shows a significant negative effect in the short-term (-0.861224, p = 0.0424) but a positive but insignificant long-run effect (1.963022, p = 0.1792). Pesticide use significantly increases maize yield, both in the short run (2.093082, p = 0.0095) and the long run (14.35734, p = 0.0000). CO2 emissions per capita (CO2PC) positively affect maize yield in the long run (18754.80, p = 0.0012), whereas agricultural CO2 emissions (CO2AG) exhibit a significant negative impact on maize yield (-22074.70, p = 0.0001). Granger causality tests indicate that rainfall, temperature, and CO2 emissions Granger-cause maize yield, with the feedback effect from agricultural emissions and productivity. These findings emphasize the need for sustainable farming practices to manage both climate change and agricultural input use effectively.